2023
DOI: 10.1002/sd.2528
|View full text |Cite
|
Sign up to set email alerts
|

Improving human development through urbanization, demographic dividend and biomass energy consumption

Abstract: The policy debate on the effects of urbanization, demographic dividend and biomass energy consumption on human development in Africa has long suffered from a scarcity of empirical evidence. This study, therefore, explores the relationship between urbanization, demographic dividend, biomass energy consumption and human development (measured by the human development index, human capital, life expectancy and infant mortality) in 33 African countries between 1990 and 2019. We employ Driscoll‐Kraay, instrumental va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 101 publications
(146 reference statements)
0
0
0
Order By: Relevance
“…Modeldeki tüm değişkenlerin insani gelişmeyi pozitif etkilediği ve insani gelişmeden yenilenebilir enerji tüketimine ve ar-ge harcamalarına doğru tek yönlü nedensellik ilişkisi bulunduğu tespit edilmiştir. Nguea (2023), 1990-2019 döneminde Afrika'da kentleşme, demografik kâr payı ve biyokütle enerjisi tüketiminin insani gelişmeye etkisini panel kantil regresyon yöntemiyle araştırmıştır. Çalışmanın bulguları, kentleşme demografik kâr payı ve biyokütle enerji tüketimindeki artışın daha yüksek bir insani kalkınma seviyesine yol açtığını ortaya koymuştur.…”
Section: Literatürunclassified
“…Modeldeki tüm değişkenlerin insani gelişmeyi pozitif etkilediği ve insani gelişmeden yenilenebilir enerji tüketimine ve ar-ge harcamalarına doğru tek yönlü nedensellik ilişkisi bulunduğu tespit edilmiştir. Nguea (2023), 1990-2019 döneminde Afrika'da kentleşme, demografik kâr payı ve biyokütle enerjisi tüketiminin insani gelişmeye etkisini panel kantil regresyon yöntemiyle araştırmıştır. Çalışmanın bulguları, kentleşme demografik kâr payı ve biyokütle enerji tüketimindeki artışın daha yüksek bir insani kalkınma seviyesine yol açtığını ortaya koymuştur.…”
Section: Literatürunclassified
“…The type of land cover in Sukoharjo Regency will also impact ecosystem services regarding providing clean water because it is related to the infiltration process and whether water can permeate the soil or develop into surface flows. Ecosystems can support life by providing benefits for living things, notably humans, related to the availability of clean water (Nguea, 2023). Water is essential for human life and has various uses with respect to households, industry, agriculture, plantations, and other activities (Ge et al, 2023).…”
Section: Ecoregionmentioning
confidence: 99%
“…Finally, the fourth part of the studies focused on the relations between urbanization and human development. It is possible to explain the relation between human development and urbanization through economic growth(Nguea, 2023). Accordingly, some studies have found that urbanization has a close relationship with economic growth (Solarin & Shahbaz, 2013;Tamang, 2013;Hong et al, 2021).…”
mentioning
confidence: 99%